India in the Indo-Pacific Understanding India's security orientation towards Southeast and East Asia - Malhotra, Aditi (International and Security Studies, 2022)
In view of the fast-changing world order, emerging countries are increasingly influencing the dynamics of regional securities. This timely and in-depth book examines India's reorienting strategic posture and describes how New Delhi's security policy in the Indo-Pacific region has evolved and expanded over the past two decades. The author argues that India's quest to leverage its geostrategic location to emerge as an Indo-Pacific actor faces multiple challenges, which create a clear divide between the country's political rhetoric and action on the ground. The author critically examines these contradictions to better situate India's security role in an increasingly fluid Indo-Pacific region.